The Contribution of Educators’ Performance to School Competitiveness: A Case Study of Islamic Elementary Schools in Riau Islands - Isropil Siregar; Kasful Anwar Us; Kemas Imron Rosadi; Rita Sahara Munte (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
This study explores the role of educators' work achievements in enhancing the competitive advantage of Integrated Islamic Elementary Schools in Riau Islands Province, Indonesia. This study involved 10 teachers and 3 school leaders from three Integrated Islamic Elementary Schools selected through purposive sampling. Drawing on qualitative case study methodology, the research investigates how professional development, innovative teaching practices, and leadership support contribute to institutional excellence. Data were collected through semi-structured interviews and analyzed using thematic analysis supported by NVivo 12 software. The findings reveal that continuous professional growth, the integration of technology-based pedagogical strategies, and transformational leadership significantly improve school competitiveness. The findings provide actionable strategies for policymakers and school leaders to implement structured professional development and leadership support systems. This study contributes to the theoretical discourse by aligning its findings with Competitive Advantage Theory, Human Capital Theory, and Innovation Theory.